Digitized walsh algorithm for reactive power estimation - Aliyu, G. (2013)
This paper presents a digitized Walsh function algorithm as an alternative approach for power components estimation with emphasis on reactive power measurement in linear and nonlinear three-phase load system. The developed algorithm was modeled on the Matlab Simulink software; linear and nonlinear loads were modeled based on practical voltage and current waveforms and tested with the proposed improved Walsh algorithm. IEEE standard 1459-2000 which is based on fast Fourier transform FFT approach was used as benchmark for the linear load system while a laboratory experiment validates the proposed improved algorithm for nonlinear load measurement. The results showed that the algorithm can effectively measure three-phase reactive power components under different load conditions. Walsh function unified approach has high inherent accuracy level as a result of coefficient features and energy behaviour representation.